Management of Village Assets in Bakiruk Villages, Malaka Tengah District, Malaka Regency East of Nusa Tenggara - Mangu, Bonivasia Julita; Angi, Yohana F.; Oematan, Herly M. (Future Science, 2023)
This research examines how well Bakiruk Villages in Indonesia manage their assets following the guidelines set by Regulation Number 1 of 2016 issued by the Minister of Home Affairs. The study uses interviews and observations to gather information and finds that village asset management could be better. Out of twelve activities involved in managing village assets, only five (planning, procurement, maintenance, use, and reporting) are done correctly according to the regulation. The remaining seven activities, including utilization, control, elimination, transfer, administration, training, security, assessment, and supervision, need to be handled properly.